2016
DOI: 10.1002/ccd.26870
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure: Initial experience with the ultraseal device

Abstract: This initial experience with the Ultraseal LAA closure device demonstrates preliminary safety and feasibility. Further larger studies with longer follow-up are warranted. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Our results show a promising feasibility and safety profile of the Ultraseal device in patients with NVAF and high risk for stroke but unsuitable for long‐term anticoagulation. Similar data were reported in other two smaller case series with shorter follow‐up time …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results show a promising feasibility and safety profile of the Ultraseal device in patients with NVAF and high risk for stroke but unsuitable for long‐term anticoagulation. Similar data were reported in other two smaller case series with shorter follow‐up time …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, procedural success was not achieved only in two patients, with an intraprocedural MI and an in‐hospital death due to pneumonia as the only in‐hospital adverse events, while no adverse events were observed at a mean follow‐up time of 166 ± 80 days, including the patients with incorrect device positioning. Similarly, in the series by Sabiniewicz et al no adverse events were reported at 1 month, while in the report by Regueiro et al, TEE performed at 45 days showed a device‐related thrombosis in one patient, without any adverse clinical events reported at follow‐up.…”
Section: Discussionmentioning
confidence: 62%
“…Further examples include needle ablation ( Sapp et al 2013 ), left atrial appendage closure ( Regueiro et al 2017 ; Saw et al 2015 ) and left atrial decompression ( Amat-Santos et al 2015 ). Some authors attributed approval of not only a procedure but also an entire program to the MDSAP.…”
Section: Resultsmentioning
confidence: 99%
“…The MDSAP approves the use of unlicensed alternatives to licensed medical devices when they are perceived to be clinically superior ( Almashham et al 2008 ; Abraham et al 2012 ; Bagur et al 2016 ; Campelo-Parada et al 2016 ; Humpl et al 2010 ; Nietlispach et al 2010 ; Raymond et al 2001 ; Regueiro et al 2017 ; Ricci et al 2017 ; Saw et al 2017 ). Peters' (2002) review of breast implants noted the availability of two types of implants: saline-filled (comprising 95% of implants), which were licensed, and gel-filled (5%), which, at the time, were unlicensed.…”
Section: Resultsmentioning
confidence: 99%
“…No episodes of bleeding, stroke, pericardial effusion or device embolization were noted at 45-day follow up. 36) …”
Section: Other Methods Of Left Atrial Appendage Occlusionmentioning
confidence: 99%